Biodiesel production from crude palm oil by transesterification process - Ahmed Kabashi, Nassereldeen; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Al-Fusaiel, A. M. A. (Asian Network for Scientific Information, 2009)
An overflow system for batch esterification of Crude Palm Oil (CPO) to obtain Palm Oil Biodiesel (POB) was developed using a batch reactor (shake flask). The alkali catalyst of potassium hydroxide had been used to carry the transestrication process with methanol; ultimately, 2 layers were form from the reaction-the lower layer of glycerol and the upper layer of methyl esters; the later layer is the targeted biodiesel. Optimization of the process was held for determining of the best possible yield of biodiesel at the end of the reaction which was 93.6%. This was carried by finding the optimal values of reaction time of 60 min, reaction temperature of 60°C, agitation speed of 250 rpm, molar ratio of methanol to oil of 10:1 (m/m) and dosage of the catalyst of 1.4 (%wt). Other experimental design and analytical tests were conducted including: density of POB at room temperature, 0.8498 kg L-1, surface tension at STP of 26.96 mN m-1, with Huh-Mason correction of 0.1 and finally free fatty acid percentage of 0.12% (equivalent to acid value of 0.26 mg KOH g-1).